Towards the development of an empirical method to assist in the selection of ground support systems in rockburst-prone conditions - Mathieu, A.; Potvin, Y.; Grenon, M. (Deep Mining 2024: Proceedings of the 10th International Conference on Deep and High Stress Mining, 2024)
Rockburst is one of the major risks in deep underground mines. It affects mining personnel safety and the operations and profitability of the mine. Although it is impossible to eliminate the probability of occurrence of a major seismic event, some measures need to be implemented to reduce the probability of seismically induced rockfalls (rockbursts). This is generally achieved with the installation of enhanced ground support systems, often referred to as dynamic ground support systems. The design of (dynamic) ground support systems in mines with rockburst-prone conditions is often based on the experience and knowledge acquired at each mine. This is used to create site-specific dynamic support designs. Stacey (2012) concluded that since the dynamic capacity of ground support systems and the demand from seismically induced dynamic loading cannot be reliably quantified, then ‘…a clear case of design indeterminacy’ results, making it ‘…impossible to determine the required support using the classical engineering design approach.’ This paper looks at the influence of combinations of ground motion factors  (GMFs) and various geotechnical conditions on the reliability of numerous ground support strategies subjected to dynamic loading conditions. The performance of seven ground support systems strategies have been investigated for a range of GMFs expressed as a function of the seismic event magnitude and distance between the seismic source and damage. The performance criterion is the survivability of the ground support system (i.e. no fall of ground, although rehabilitation may be required). A reliability index was developed to classify the reliability of the performance. Results are shown as a preliminary version of a ‘survivability matrix’ which can provide insight into the selection of ground support systems in underground mines with rockburst-prone conditions.